2006
DOI: 10.1007/s00421-006-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Substrate utilization during prolonged exercise with ingestion of 13C-glucose in acute hypobaric hypoxia (4,300 m)

Abstract: Energy substrate oxidation was measured using indirect respiratory calorimetry combined with tracer technique in five healthy young male subjects, during a 80-min exercise period on ergocycle with ingestion of 140 g of (13)C-labelled glucose, in normoxia and acute hypobaric hypoxia (445 mmHg or 4,300 m), at the same relative [77% V(.-)((O)(2)(max))] and absolute workload (161+/-8 W, corresponding to 77 and 54% V(.-)((O)(2)(max)) in hypoxia and normoxia). The oxidation rate of exogenous glucose was not signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 36 publications
(69 reference statements)
9
55
7
1
Order By: Relevance
“…Several previous studies have indicated that hypoxia increases carbohydrate oxidation (Brooks et al 1991; Roberts et al 1996a, [b]). Enhanced reliance on plasma glucose oxidation for energy production under hypoxic conditions leads to the promotion of carbohydrate oxidation during rest or exercise (Brooks et al 1992; Peronnet et al 2006). Although the present results do not support this suggestion, previous studies have indicated enhancement of carbohydrate oxidation by hypoxia in elite endurance athletes, with marked differences between endurance athletes and sedentary individuals (Havel et al 1963, 1964; Hurley et al 1986; Bircher and Knechtle 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have indicated that hypoxia increases carbohydrate oxidation (Brooks et al 1991; Roberts et al 1996a, [b]). Enhanced reliance on plasma glucose oxidation for energy production under hypoxic conditions leads to the promotion of carbohydrate oxidation during rest or exercise (Brooks et al 1992; Peronnet et al 2006). Although the present results do not support this suggestion, previous studies have indicated enhancement of carbohydrate oxidation by hypoxia in elite endurance athletes, with marked differences between endurance athletes and sedentary individuals (Havel et al 1963, 1964; Hurley et al 1986; Bircher and Knechtle 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present results do not support this suggestion, previous studies have indicated enhancement of carbohydrate oxidation by hypoxia in elite endurance athletes, with marked differences between endurance athletes and sedentary individuals (Havel et al 1963, 1964; Hurley et al 1986; Bircher and Knechtle 2004). Furthermore, most previous studies (Brooks et al 1991, 1992; Roberts et al 1996a, [b]; Peronnet et al 2006) used severe hypoxia (altitude > 4000 m). Therefore, differences in the levels of hypoxia (i.e., altitude) between previous studies and the present study may explain the contradictory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain perfusion of O 2 during hypoxic exercise, breathing frequency (Bf), minute ventilation (trueV˙E), and heart rate (HR) are all elevated above similar workloads performed at sea-level (Mazzeo, 2008). However, these physiological adjustments are limited as maximal oxygen uptake (trueV˙O 2max ) decreases at a rate of approximately 7% for each 1,000-m increase in elevation above sea-level (Fulco et al, 1998; Peronnet et al, 2006; Mazzeo, 2008; Saunders et al, 2009). During constant-load exercise, both the absolute rate of carbohydrate oxidation (CHOox) and its relative contribution to the fuel mixture are elevated in hypoxia compared to normoxia (Wagner et al, 1986; Sutton et al, 1988; Lundby and Van Hall, 2002; Peronnet et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, these physiological adjustments are limited as maximal oxygen uptake (trueV˙O 2max ) decreases at a rate of approximately 7% for each 1,000-m increase in elevation above sea-level (Fulco et al, 1998; Peronnet et al, 2006; Mazzeo, 2008; Saunders et al, 2009). During constant-load exercise, both the absolute rate of carbohydrate oxidation (CHOox) and its relative contribution to the fuel mixture are elevated in hypoxia compared to normoxia (Wagner et al, 1986; Sutton et al, 1988; Lundby and Van Hall, 2002; Peronnet et al, 2006). Such a shift in substrate oxidation helps to maintain energy supply in reduced O 2 environments due to the greater energy yield per liter of O 2 consumed when glucose is completely oxidized compared to fatty acids and amino acids (Hochachka, 1988; Brooks et al, 1991b; Mazzeo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Il existe également peu de données systématiques sur l'effet du mode d'administration des glucides exogènes [bolus vs doses (Massicotte et al, 1996a) ; ingestion avant vs pendant l'exercice Caron et al, 2004;Krzentowski et al, 1984a) ; effet de la concentration de la solution ingérée (Jandrain et al, 1989;Jentjens et al, 2004bJentjens et al, , 2006Moodley et al, 1992)] sur leur oxydation. Un certain nombre d'études se sont penchées, par contre, sur l'effet de l'entraînement Jeukendrup et al, 1997;Krzentowski et al, 1984b;Péronnet et al, 2009;van Loon et al, 1999), de l'état nutritionnel (Ravussin et al, 1979), de certains facteurs environnementaux [froid (Galloway et al, 2001), chaud (Jentjens et al, 2006(Jentjens et al, , 2002, hypoxie (Péronnet et al, 2006)] et de certains nutriments ou agents pharmacologiques dont on sait qu'ils interfèrent ou pourraient interférer avec la digestion et l'absorption des glucides et la sélection des substrats [acarbose qui inhibe les glucosidases (Gerard et al, 1986), sodium (Massicotte et al, 1996b) qui pourrait faciliter l'absorption du glucose par le « sodium-glucose transporter 1 » (SLGT1) , métoclopramide qui accélère la vidange gastrique (Massicotte et al, 1996b), acipimox qui bloque la lipolyse (Gautier et al, 1994) ; caféine (Desbrow et al, 2009;Hulston et Jeukendrup, 2008;Yeo et al, 2005)]. …”
Section: Vue D'ensemble Des éTudesunclassified